Implementation of the DoD Diversity and Inclusion Strategic Plan A Framework for Change Through Accountability - Lim, Nelson (RAND Corporation, 2013)
Provides a framework that the Department of Defense (DoD) can use to organize the strategic initiatives outlined in its 2012 Diversity and Inclusion Strategic Plan. The framework emphasizes the creation of an enduring accountability system and categorizes DoD's strategic initiatives along three key dimensions-compliance, communication, and coordination ("the three Cs")-and prioritizes them across time-short, medium, and long term.